Review: Unraveling the origin of the structural and functional diversity of plant cystatins. (August 2022) - Balbinott, Natalia; Margis, Rogerio
Abstract: The regulation of protease activity is a critical factor for the physiological balance during plant growth and development. Among the proteins involved in controlling protease activity are the cystatins, well-described inhibitors of cysteine proteases present in viruses, bacteria and most Eukaryotes. Plant cystatins, commonly called phytocystatins, display unique structural and functional diversity and are classified according to their molecular weight as type-I, -II, and -III. Their gene structure is highly conserved across Viridiplantae and provides insights into their evolutionary relationships. Many type-I phytocystatins with introns share sequence similarities with type-II phytocystatins. New data shows that they could have originated from recent losses of the carboxy-terminal extension present in type-II phytocystatins. Intronless type-I phytocystatins originated from a single event shared by flowering plants. Pieces of evidence show multiple events of gene duplications, intron losses, and gains throughout the expansion and diversity of the phytocystatin family. Gene duplication events in Gymnosperms and Eudicots resulted in inhibitors with amino acid substitutions that may modify their interaction with target proteases and other proteins. This review brings a phylogenomic analysis of plant cystatin evolution and contributes to a broader understanding of their origins. A complete functional genomic analysis among phytocystatins and their roles in plant development and responses to abiotic and biotic stresses remains a question to be fully solved. Graphical Abstract: ga1 Highlights: A carboxy-extended phytocystatin is ancestral of part of current type-I phytocystatins. Two major type-II phytocystatin duplications took place in Gymnosperms and Eudicots. Second domain loss and gene duplications led to the diversity of phytocystatins. Type-I phytocystatin radiation occurred in association with intron deletion.